Nutritional knowledge, insulin resistance, and the risk of orthorexia nervosa: a comparative cross-sectional study among polish women - Staśkiewicz-Bartecka, Wiktoria; Masłoń, Karolina; Kołodziejczyk, Aleksandra; Białek-Dratwa, Agnieszka; Kiciak, Agata; Jaruga-Sękowska, Sylwia; Dobkowska-Szefer, Daria; Grajek, Mateusz; Kowalski, Oskar; Kardas, Marek (Frontiers in Public Health, 2025)
BackgroundThe global rise in insulin resistance has led to an increased emphasis on dietary modifications as a primary strategy for its management. While such interventions are essential for improving metabolic health, they can also contribute to heightened nutritional knowledge. However, this increased focus on diet may inadvertently lead to the development of disordered eating patterns, including orthorexia nervosa. This study aimed to determine the level of nutritional knowledge regarding proper eating habits among women with insulin resistance and to assess the relationship between this knowledge and the risk of developing orthorexia nervosa.MethodsThe study was using the Computer-Assisted Web Interview method, involving 133 female participants from a primary care clinic in Katowice, Poland. Of these, 101 women had a medically confirmed diagnosis of insulin resistance, and 32 were healthy controls. Data were collected using an online survey, which included a demographic section, a 15-item questionnaire to assess nutritional knowledge, and the ORTO-15 tool to evaluate orthorexia nervosa risk.ResultsWomen with insulin resistance had significantly higher Body Mass Index values and demonstrated greater nutritional knowledge than their healthy counterparts. However, 56.44% of women with insulin resistance were at risk of orthorexia nervosa, compared to 15.63% of the control group. Increased dietary knowledge in women with insulin resistance was also associated with a higher risk of developing orthorexic behavior.ConclusionThe findings indicate that while women with insulin resistance benefit from improved nutritional knowledge in managing their condition, this knowledge may simultaneously increase their risk of developing orthorexia nervosa. Balancing the promotion of healthy eating habits with strategies that prevent the emergence of distorted eating behaviors is crucial. Future interventions should emphasize flexibility, psychological support, and individualized guidance to ensure both metabolic and mental well-being.